ANALISIS KUALITAS AIR DI KALIMANTAN SELATAN SEBAGAI BAHAN CAMPURAN BETON - Novitasari Novitasari; Ulfa Fitriati; M. Mirza Peradana (INFO-TEKNIK, 2014)
SNI 03-2847-2002 requirement that the water used in the concrete mix should be clean and free of damaging substances containing oil, acids, alkalis, salts, organic matter, or other substances harmful to concrete or reinforcement. But in fact, often we see the use of water as an ingredient in concrete mixtures that do not follow the requirements of SNI. Work in the field often use water that is in that location without regard to the content that is in them that would negatively affect the compressive strength of the concrete. The purpose of this study was to determine the quality of water contained in the PDAM water, brackish water in the estuary of the Barito, peat water in the area Sambang Lihum, Martapura river water, Polder Alabio water, and water wells in the area Banjarbaru.This test uses several tools, pH Meter to determine levels of acid and alkali in the water, EC Meter to determine levels of salt in the water, and Water Quality Meters to determine water quality. As for the sulfate content in water testing performed Basic Laboratory Faculty of Science, University of Mangkurat, Banjarbaru.On water quality testing, only Brackish Water samples in estuaryof the Barito ineligible pH and salinity, whereas the content of TDS (Total Dissolved Solids) Brackish Water samples in the estuary of the Barito and Water Wells in Banjarbaru ineligible the standard. Keywords: Quality of water, brackish water, the compressive strength of concrete